EYELID RECONSTRUCTION IN DERMATOLOGIC SURGERY - Leite, Inês (2011)
The reconstruction of surgical defects of eyelids is challenging due to the anatomic complexity of eyelids allied with its aesthetic and functional significance. Since skin cancer is frequent on this region, the dermatologic surgeon have to be aware of the anatomical particularities of eyelids and the reconstructive options available in order to achieve the better aesthetic and functional results. The authors review the surgical anatomy of eyelids, the local anesthesia techniques and the main reconstructive options according to the type and localization of the surgical defect.